Emerging apologetics : Themes in contemporary African youth ministry: A Kenyan perspective - Muriithi Ndereba, Dr. Kevin (Stellenbosch Theological Journal, 2022)
Contemporary Christian ministry and theological education in Africa cannot neglect her children and young people. Engaging effectively with the children and youth in Africa's cities presents a rising challenge to scholars and practitioners. In addition to the developmental issues surrounding children and youth, there are worldview issues at play among young people. Urban African cities like Nairobi contain a mixture of African traditional religious worldviews, modern worldviews, and postmodern worldviews. This means that Christian ministry with the emerging generations will often take an apologetic mode. The scholarly literature on apologetics in the continent is scanty. Further, much of the research is merely theoretical and lacks empirical insight from practical ministry. This article will use an empirical methodology among African church leaders to collect salient themes in the discipline and practice of apologetics and draw conclusions for ministry and theological education.